2018
DOI: 10.2215/cjn.13181117
|View full text |Cite
|
Sign up to set email alerts
|

Variations in 24-Hour BP Profiles in Cohorts of Patients with Kidney Disease around the World

Abstract: In a large, multinational database, the prevalence of masked and sustained hypertension varied across cohorts independent of important comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
(46 reference statements)
4
22
0
Order By: Relevance
“…More recently, a study from the International Database of Ambulatory BP in Renal Patients collaborative group showed wide variations in 24-hour BP profiles in patients with nondialysis CKD from 7 studies in 4 countries. 33 Like ours, that study showed poor BP control in European cohorts, either according to clinic BP or to combined clinic and ambulatory BP. Its finding that European participants had the highest likelihood of white-coat hypertension suggests that clinic BP may be particularly overestimated in this population.…”
Section: Discussionsupporting
confidence: 55%
“…More recently, a study from the International Database of Ambulatory BP in Renal Patients collaborative group showed wide variations in 24-hour BP profiles in patients with nondialysis CKD from 7 studies in 4 countries. 33 Like ours, that study showed poor BP control in European cohorts, either according to clinic BP or to combined clinic and ambulatory BP. Its finding that European participants had the highest likelihood of white-coat hypertension suggests that clinic BP may be particularly overestimated in this population.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, the prevalence of white coat hypertension contributing to ATRH was 39% in a Spanish study (24). This is consistent with previously reported differences in white coat hypertension across different countries and racial-ethnic groups in patients with CKD (25). The reasons underlying these differences remain unclear and require further study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have compared the prevalence of comorbidities and incidence of CKD complications across populations with CKD from different countries. 1,5,33,34 A study of 5 international CKD cohorts reported a variable prevalence of masked and sustained hypertension assessed by 24-hour blood pressure monitoring despite adjustments for comorbidities and levels of eGFR. 33 Another study explored differences in the incidence of ESRD between white individuals in the United States and those from Norway, standardized for age and sex.…”
Section: Contrast With Other International Comparisonsmentioning
confidence: 99%